Development, validation, and reliability testing of the standard treatment workflow checklist - Prudhvi Teja, Rangisetti Naga; Thimmiah, Arjun; Kachroo, Kavita; Moinudeen, Syed Abdul Khader; Sahithya, Vanjavakam; Sharma, Jitendra; Grover, Ashoo (International Journal Of Community Medicine And Public Health, 2024)
Background: Standard Treatment Workflows (STWs) are systematically developed documents designed to enhance clinical care and patient outcomes. Validating these workflows is essential for their adoption across diverse clinical settings. This study aimed to develop and validate a checklist for evaluating STWs. Methods: The study was conducted in three phases. Initially, items were generated through a comprehensive literature review and expert consultations, followed by pre-testing (N=50). In the second phase, content validation (N=43) was performed using the Content Validity Index (CVI) and Content Validity Ratio (CVR) to assess the relevancy and essentiality of each item. Item-level (I-CVI) and scale-level (S-CVI) indexes were calculated. Items were accepted, modified, or rejected based on these scores. In the third phase, pilot testing (N=30) assessed the checklist's reliability and calculated Cronbach's alpha. Results: The final checklist comprised 33 close-ended and one open-ended items. Each item was deemed relevant and essential, with I-CVIs ranging from 0.96 to 1.00 and S-CVI/UA and S-CVI/Ave values of 0.83 and 0.99, respectively. CVR values ranged from 0.85 to 1.00, with an average CVR of 0.97. Reliability testing yielded Cronbach’s alpha values of 0.863 and 0.961 for the two parts of the checklist. Conclusions: The developed checklist is valid and reliable, with satisfactory CVI, CVR, and Cronbach’s alpha values. It can be used as a standard tool for assessing STW validation and effectively capturing essential aspects of STW evaluation.